2022
DOI: 10.3389/fonc.2022.1014786
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients and COVID-19 vaccination, from safety to protocol adherence: A real-life setting report

Abstract: BackgroundThe SARS-CoV-2 pandemic has slowed down cancer prevention and treatment strategies; consequently, cancer patients are prioritized to get the COVID-19 vaccines. Being constantly threatened by a new outbreak, the dive within the immunogenicity response is of great value; nonetheless, evaluating the side effects of these vaccines on fragile patients will assure their adherence to the vaccination protocol.ObjectivesThis study sets out to investigate the adverse events reported about the vaccine according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, a Mendelian randomization study ( Li et al, 2022 ) reported that cancers might have no causal effect on increasing COVID-19 risk. A real-life setting report ( Lamtai et al, 2022 ) recommended that cancer patients should take the COVID-19 vaccines, which might reduce the mortality rate in cancer patients with COVID-19 ( Safari et al, 2022 ), and should follow their vaccination schemes under the supervision of their treating physicians. Vitamin D supplementation and sun exposure may also be helpful for cancer patients during the COVID-19 pandemic ( Vieth, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a Mendelian randomization study ( Li et al, 2022 ) reported that cancers might have no causal effect on increasing COVID-19 risk. A real-life setting report ( Lamtai et al, 2022 ) recommended that cancer patients should take the COVID-19 vaccines, which might reduce the mortality rate in cancer patients with COVID-19 ( Safari et al, 2022 ), and should follow their vaccination schemes under the supervision of their treating physicians. Vitamin D supplementation and sun exposure may also be helpful for cancer patients during the COVID-19 pandemic ( Vieth, 2022 ).…”
Section: Introductionmentioning
confidence: 99%